Effect of systematic application of mineral fertilizers and long-term aftereffect of liming on the organic matter of light-grey forest soil - N. A. Kodochilova; T. S. Buzynina; L. D. Varlamova; E. A. Katerova (Аграрная наука Евро-Северо-Востока, 2020)
The studies on assessment of changes in the content and composition of soil organic matter under the influence of the systematic use of mineral fertilizers (NPK)1, (NPK)2, (NPK)3 against the background of the aftereffect of single liming in doses of 1.0 and 2.0 h. a. (control – variants without fertilizers and lime) were conducted in the conditions of the Nizhny Novgorod region in a long – term stationary experiment on light-grey forest soil. The research was carried out upon comple-tion of the fifth rotation of the eight-field crop rotation. The results of the study showed that for 40 years (from 1978 to 2018) the humus content in the soil (0-20 cm) decreased by 0.19-0.52 abs. % in variants as compared to the original (1.60 %); though, humus mineralization was less evident against the background of long-term use of mineral fertilizers compared to non-fertilized control. The higher humus content in the topsoil was noted in the variants with minimal (NPK)1 and increased (NPK)2 doses of fertilizer – 1.41 and 1.25 %, respectively. The humus content in non-fertilized soil and when applying high (NPK)3 doses of mineral fertilizers was almost identical – 1.08-1.09 %. The predominant group in the composition of humus were humic acids, the content of which in the experiment on average was 37.8 % of the total carbon with an evident decrease from 42.6 % in the control to 31.8% when applying increased doses of mineral fertilizers. The aftereffect of liming, carried out in 1978, was unstable and did not significantly affect the content and composition of soil organic matter.